The clinical biochemical and hematological profile of scrub typhus meningoencephalitis - Souvik Sarkar; Soumya Sarathi Mondal; Enamul Hossain; Souvik Kumar Das; Rahul Kumar; Sanjay Kumar Mandal (Asian Journal of Medical Sciences, 2023)
Background: Scrub typhus is a zoonotic infectious disease caused by the Gram-negative coccobacillus Orientia tsutsugamushi. Meningoencephalitis occurs in two-thirds of all the infected cases.